American Democracy in Distress: The Failure of Social Education - Neumann, Richard (JSSE - Journal of Social Science Education, 2017)
The primary purpose of this essay is to further understanding of the relationship between social education programs in public schools in the United States and the health of its democracy.  A secondary purpose is to encourage reflection on the condition of democracy in other countries and the adequacy of social education programs in these countries in preparing youths for democratic citizenship.  Extant data on social education in American public schools are analyzed and discussed in relation to selected social and economic conditions and the health of democracy in the United States.  The conclusion is that social education programs in the United States do not adequately prepare young people for political participation and this deficiency has contributed significantly to distress in American democracy.